Our Girl Wins Award - Sunday Star, (2008)
THE Star journalist Tan Shiow Chin is the recipient of the second IDRC-SciDev.Net Science Journalism Award. The US 58.500 (RM194,337) award consists of a six month internship with SciDev.Net (Science and Development Network - a science news website) which will al ow Tan to develop her professional skills s a science journalis.